Case Report: Incidental finding of an atresia of the inferior vena cava—a challenge for cardiac surgery - Buech, Joscha; Radner, Caroline; Fabry, Thomas; Rutkowski, Simon; Hagl, Christian; Peterss, Sven; Pichlmaier, Maximilian A. (Frontiers in Cardiovascular Medicine, 2024)
Inferior vena cava atresia is a rare and usually assymaptomaticasymptomatic condition. However, when these patients undergo cardiac surgery, it can present an unexpected and challenging situation for the surgeon. Specifically, adequate venous drainage during cardiopulmonary bypass (CPB) is a critical issue here and may require an extension of cannulation strategies. Adequate preoperative diagnostics, ideally with imaging modalities such as CT angiography or MRI, are required for optimal surgical planning. Here, we describe a rare case of thoracic ascending aortic aneurysm with concomitant inferior vena cava atresia that was successfully operated on. With adequate preoperative planning, we were able to perform an unproblematic operation without unforeseen complications with standard initialization of cardiopulmonary bypassCPB.